Perceptions and Beliefs on Aging and Their Impact on Elderly General Health: An Appraisal of Self-Regulation Model - Ebrahim Masoudnia (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: The beliefs and perceptions regarding aging have an important effect on the well-being of the elderly population. A self-regulation model is one of the useful theoretical models to explain the role of perceptions and beliefs about aging in determining the health outcomes of elderly people. The aim of this study was to determine the relationship between aging-related perception and elderly general health in self-regulation framework. Methods & Materials: This study was conducted in a descriptive survey design. The elderly participants were selected using the most convenient sampling method from the nursing homes and communities in Rasht city. Data was collected from 300 elderly people, of which 144 males and 156 females. The aging perception questionnaire (APQ) and general health questionnaire (GHQ) were used as the measuring tools. Results: A significant positive correlation was noted between the most components of the perception to aging such as chronic and cyclical timeline, consequences positive and negative, emotional representations, control positive and negative and other components of elderly general health. Hierarchical multiple regression analysis showed that the components of aging perception i.e. control positive and negative, consequences negative and cyclical time-line, attributed to 31.2% of the variance in elderly general health. Conclusion: The perception toward aging is one of the important determinants and key predictors of elderly general health. Also, the self-regulation model proves to be an appropriate framework to explain the role of beliefs, perceptions, and understanding of the experiences of aging on the physical and mental health status of the elderly.